2014
DOI: 10.1007/s10517-014-2589-7
|View full text |Cite
|
Sign up to set email alerts
|

On Statistical Relationship between ADRA2A Expression and the Risk of Breast Cancer Relapse

Abstract: The search for novel parameters to predict the risk of relapse in breast cancer was conducted. Significant correlation between the risk of relapse and α-2A adrenergic receptor (ADRA2A) expression was revealed using public microarray datasets. This relationship was confirmed by validation on independent microarray dataset. It was found that when assessing the risk of BC relapse, the accuracy of prediction based solely on the expression of ADRA2A gene is close to that made using OncotypeDX and MammaPrint test sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…Studies conducted using cDNA microarrays reported the presence of SQLE in sets of differentially expressed transcripts in breast cancers [6] and lung squamous cell carcinoma [7]. Recent studies have shown that SQLE is differentially expressed in lung cancer [7,8], breast cancer [9,10], prostate cancer [11,12], hepatocellular carcinoma [13], and esophageal cancer [14]. SQLE overexpression or copy number variation is significantly associated with tumor progression, metastases and unfavorable outcomes in prostate cancer and breast cancer patients [6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted using cDNA microarrays reported the presence of SQLE in sets of differentially expressed transcripts in breast cancers [6] and lung squamous cell carcinoma [7]. Recent studies have shown that SQLE is differentially expressed in lung cancer [7,8], breast cancer [9,10], prostate cancer [11,12], hepatocellular carcinoma [13], and esophageal cancer [14]. SQLE overexpression or copy number variation is significantly associated with tumor progression, metastases and unfavorable outcomes in prostate cancer and breast cancer patients [6,15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have already been conducted to explore the potential role of the dysregulation of SQLE in BC (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Polycarpou-Schwarz et al (16) identified a new microprotein gene, Cancer-Associated Small Integral Membrane Open reading frame 1 (CASIMO1), utilizing a microarray approach.…”
Section: Discussionmentioning
confidence: 99%
“…Kim et al (21) found that SQLE was one of the important genes for BC metastasis based on a standardized pathway-based approach. Shkurnikov et al (22) searched for novel parameters predicting the risk of relapse in patients with BC using public microarray datasets, revealing that SQLE expression was significantly associated with the risk of relapse in patients with BC. Parada et al (23) examined racial differences in the expression levels of eight genes, including SQLE, and their associations with the risk of BC recurrence among white and black women with BC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reports [24,28] showed that stimulation of α2-adrenoceptors by the highly selective α2-adrenoceptor agonists dexmedetomidine and clonidine enhance breast cancer cell proliferation, tumor growth, and metastasis, and this could be reversed by the α2-adrenoceptor antagonists yohimbine and rauwolscine. In addition, Shkurnikov and colleagues [29] found a significant correlation between the risk of breast cancer relapse and expression of α2A-adrenoceptors. The mechanism of α2-adrenoceptor-modulating cancer progression has not yet been clearly elucidated.…”
Section: β-Adrenoceptor Modulatorsmentioning
confidence: 99%